Freedom and Values: A Reflection Based on the Axiology of J. M. Méndez - Barraca Mairal, Javier (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This text reflects on the theme of freedom and its relationship with values. To do this, it shows the original approach to this issue present in the thought of the current Spanish philosopher J. M. Méndez. According to the characteristic thinking of this author, freedom does not represent a value but the gateway or the very possibility of participation in any ethical value, as postulated by his axiological liberalism.